Towards a critical sociolinguistics - Singh, Rajendra (Amsterdam studies in the theory and history of linguistic science. Current issues in linguistic theory ;, 1996)
This collection of twelve essays, some of which have been written specifically for this volume by well-known European and North-American sociolinguists, reflects an increasing recognition within the field that sociological and theoretical innocence can no longer be underwritten by it, and offers a multi-pronged and multi-methodological way to move towards a critical, reflexive, and theoretically responsible socio-linguistics. It explores, with courage and sensitivity, some very important areas in the enormous space between Bloomfieldian 'idiolect' and Chomskyan 'UG' in order to situate the hum.